A hexa‐band dual‐sense circularly polarized antenna for WLAN/Wi‐MAX/SDARS and C‐band applications. Issue 4 (10th November 2018) - Alam, Maksud; Mainuddin,; Kanaujia, B.K.; Beg, M.T.; Kumar, Sachin; Rambabu, Karumudi
Abstract: In this article, a compact single fed hexa‐band circularly polarized (CP) monopole antenna using split ring resonators (SRRs) on the partial ground plane is designed and experimentally investigated. The loaded SRR elements generate multiple circularly polarized bands along with a reduction in antenna size. The multiband can be controlled by changing the configuration of SRRs and their position on the ground plane without altering the monopole radiator. To illustrate the CP mechanism and multiband operation of the proposed configuration, the surface current density has been studied. The antenna is fabricated on RT Duroid 5880 substrate of permittivity 2.2 with a total size of 47 × 40 × 1.57 mm 3 . Compared with the existing antenna designs, the proposed structure is compact and demonstrates improved multiband performance with circular polarization.